Responses of Flexible Pavement Structure to Variation of Load Type, Material Characteristics, and Service Life using Kenlayer Program - Setyo Ayuningtyas, Kardina Nawassa; Subagio, Bambang Sugeng (Jurnal Teknik Sipil, 2019)
One of the pavement types often used in Indonesia is flexible pavement. Many methods and programs can be used for flexible pavement structure analysis, such as analytical method using Kenlayer program. Variation of load type (single axle, dual-tandem, and dual-tridem) and material characteristics (linear-elastic, and nonlinear-elastic) used to approach the real condition in the field. In addition, repetition load during service life to failure criteria of flexible pavement structure with several variations of its design attributes need to be considered to gain more understanding for its pattern and relationship. This research aims to analyse the relationship for variation of load type, material characteristics to its response; and failure criteria in service life analysis with some attribute variant which can be used to optimize each attribute in future. Based on the results from Kenlayer program for variation of load type, the biggest response of deflection is resulted from dual-tridem followed by dual-tandem while load type variant has insignificant response to stress and strain. The variation of material characteristics indicates that for 3- layer pavement system: linear-linear-linear material (L-L-L) has higher value of flexible pavement responses compared to linear-nonlinear-nonlinear material (L-NL-NL) hence the nonlinear material is recommended for 2nd and 3rd layer. In case of service life analysis, failure criteria mostly resulted from permanent deformation for variation of loads, and resilient modulus of each layer, nevertheless the different result is observed in thick layer of surface and base course where fatigue cracking is more dominant and the optimal condition is when fatigue cracking graph intersect with permanent deformation. Salah satu jenis struktur perkerasan yang paling banyak digunakan di Indonesia adalah struktur perkerasan lentur. Terdapat banyak metode dan program dapat digunakan untuk analisa struktur perkerasan lentur, salah satunya adalah Metode Analitis dengan menggunakan program Kenlayer. Variasi tipe pembebanan (single-axle, dualtandem, dan dual-tridem) serta karakteristik material (linear-elastik, dan nonlinear-elastik) digunakan sebagai pendekatan pada kondisi lapangan. Beban repetisi selama umur layan terhadap kriteria keruntuhan dengan beberapa variasi pada atribut desain struktur perkerasan lentur perlu dianalisis untuk mendapatkan pemahaman yang lebih dalam serta mendapatkan pola perilaku dan hubungannya. Penelitian ini bertujuan untuk menganalisis hubungan pada berbagai variasi beban, karakteristik material terhadap respon struktur, serta kriteria keruntuhan pada analisis umur layan dengan beberapa variasi atribut yang digunakan. Berdasarkan hasil yang didapatkan dar program Kenlayer, untuk variasi beban didapatkan titik respon maksimum adalah berada pada (0; 17,15) pada single-axle dan dual-tandem, serta (121,9; 17,15) pada dual-tridem. Defleksi terbesar terjadi pada beban dualtridem diikuti dengan dual-tandem, dimana variasi dari beban tersebut tidak berpengaruh secara signifikan terhadap tegangan dan regangan yang terjadi. Variasi karakteristik material menunjukkan bahwa material linear (L-L-L) menghasilkan nilai respons yang lebih besar dibandingkan dengan material non-linear (L-NL-NL). Dalam hal analisis umur layan, kriteria keruntuhan yang terjadi sebagian besar disebabkan oleh deformasi permanen pada variasi beban dan modulus resilien pada masing-masing layer, namun hasil yang berbeda didapatkan pada layer permukaan dan layer dasar yang tebal dimana kriteria retak lelah lebih dominan.